Podstawowe założenia glottodydaktyki Bronisława Rocławskiego i jej interdyscyplinarne zastosowanie w nauczaniu początkowym i logopedii – przegląd literatury przedmiotowej - Rocławska-Daniluk, Małgorzata; Kisiel, Weronika (Interdyscyplinarne aspekty diagnozy i terapii logopedycznej, 2020)
The system (or otherwise: method) of Bronisław Rocławski’s glottodydactics has been described in many scientific publications. An overview of selected scientific studies on this subject published in Poland after 1996 presents the most important glottodydactics topics. In the summary, the authors made insights about the education crisis, as well as positive attitudes to support.